Dampak Pernikahan Dini Terhadap Keberlangsungan Rumah Tangga (Studi Kasus di Kecamatan Gemawang) - Retno Kunratih (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2019)
This paper describes the phenomenon of early marriage in the Gemawang sub-district which is still prevalent. In accordance with the locus, this study uses a descriptive qualitative approach. The author found the practice of early marriage due to several very dominant factors. Community culture, level of education, and patterns of child interaction and economic problems that underlie the practice of early marriage. The impact of this practice is that many household life experiences many very serious problems / problems. The practice of domestic violence which leads to divorce often colors the case in the community. Departing from the problems that arise, the author will try to find solutions to existing problems. Preventive efforts, strengthening knowledge and awareness of the importance of building moral responsibility in society are solutions to the freezing of people’s thinking. By giving rise to people’s understanding of the essence of marriage, which is to create a sakinah, mawadah wa rahmah community, the ideal hopes of baiti jannati will be realized.